Identification and analysis of the elements and functions integrable in integrated management systems - Nunhes, Thaís Vieira [UNESP] (2017)
The purpose of this article is to characterize and discuss the elements and functions most commonly integrated in Brazilian companies certified by the management systems ISO 9001, ISO 14001 and OHSAS 18001 and to identify the benefits and difficulties from integration. This study contributes with suggestions of achievements to overcome the major difficulties and challenges faced during the integration process. In order to support the research, the theoretical framework was conducted comprising certifiable management systems (ISO 9001, ISO 14001 and OHSAS 18001) and Integrated Management Systems. The study was based on a qualitative approach supported by an analysis in the practical context, which examined the results of fourteen case studies in Brazilian industrial companies. The development of the research involved three visits in each one of the companies studied. The results indicated the most integrated elements and functions in the companies studied are the high management responsibility, work instructions, control of documents and records, internal communication and structure and accountability. Further, the benefits of integration were the improvement in efficiency of operations and internal communication, greater agility in the decision-making process, increase in the quality of goods and services produced or provided and increase in reliability of the products and processes. The main difficulties were the complexity of integration process and the high amount of human and financial resources spent on implementation.